Habitat Characteristics of Northern Bobwhite Quail-Hunting Party Encounters: A Landscape Perspective - William K. Michener; Jimmy B. Atkinson; Don G. Edwards; Jeffrey W. Hollister; Paula F. Houhoulis; Paula M. Johnson; Robert N. Smith (National Quail Symposium Proceedings, 2017)
Landcover data and bobwhite hunting records were used to assess both hunter habitat preferences and the frequency of northern bobwhite encounters by hunting parties in relation to habitat composition during the 1994-1995 and 1995-1996 hunting seasons at the Joseph W. Jones Ecological Research Center in southern Georgia. Patterns of habitat use by hunters, and the frequency of bobwhite encounters varied within and between years, depending on habitat quality, food availability, and other factors. Landscape-scale analyses of standardized bobwhite covey densities (based on coveys pointed in the field) and habitat composition and configuration for the 1994-1995 hunting season revealed that bobwhite densities were: (1) positively associated with the overall percentage agriculture and food plot habitat (reaching a maximum at 30-35% agriculture); and (2) positively associated with edge complexity, and positively associated with agricultural mean patch size [reaching a maximum at 2-3 hectares (5-6 acres)]. Consequently, larger food plots may be more important for increasing bobwhite encounter rates than numerous very small food plots [ < 0.1 hectares (0.25 acres)]. Results of this, and related ongoing studies, have important implications for both landscape design and multiple use resource management. activities in the context of northern bobwhite habitat management in southern upland pine forest ecosystems.